Qualitative and quantitative characteristics of the alga Eutreptia lanowii (steuer) in relation to the coastal pollution phenomenon - Mihnea, Pia Elena (Cercetări Marine - Recherches Marines, 2026)
Data on the biological cycle and quantitative variations in the species Eutreptia lanowii are here presented. The correlation of this organism with the environmental factors proves its occurrence and development because of the sea water quality modification in the coastal zone.